Hobby Store / Amirul Shah Abdullah ... [et al.] - Abdullah, Amirul Shah; Adnan, Mohammad Hakim; Mohd Ribuan, Mohd Khalid; Mohd Daud, Ahmad Rizal (Faculty of Accountancy, 2001)
Our business name is Hobby Store. The type of business that we will be doing is selling radio control models such airplanes, helicopters, cars and watercrafts and we also offer services related to the business. This type of business has been in the market of Malaysia for a long time ago. We have make a study about the business of radio control at a company named Hobby World Sdn Bhd. This company was establish since 1981. This company was known to be the pioneer company of the official distributor of radio control models in Malaysia. The models are imported from other countries such as Japan, United States of America, Korea and others .There are no manufacturer of this radio control models in Malaysia. All are imported things.